Application of polyethylene glycol-coated iron oxide nanoparticles for magnetic solid phase extraction of copper from seawater samples and its determination by graphite furnace atomic absorption spectrometry using response surface methodology for optimization of extraction. Issue 4 (21st April 2021) - Khayyat-Sarkar, Zahra; Hashemi, Sayyed Hossein; Jamali Keikha, Ahmad; Kaykhaii, Massoud
Abstract: In this research, a novel solid phase extraction method combined with graphite furnace atomic absorption spectrometry has been employed for the extraction and trace determination of copper in tap and seawater samples. The technique was based on poly ethylene glycol-coated iron oxide nanoparticle as adsorbent for solid phase extraction of copper ions. Optimal conditions including pH, extraction and desorption time, concentration and volume of eluent, temperature, volume of sample, amount of PEG and sorbent were investigated and optimized using both the one-variable-at-a-time method and response surface methodology. Under the optimal experimental conditions, the calibration graph was linear in range of 0.5–125.0 µg/L with detection limit of 6 ng/L. Good enrichment factor of 121 folds for the analyte was obtained. The repeatability of the method was satisfactory (RSD ≤ 4.8%). Finally a few seawater samples of Chabahar Bay (Southeast Iran) were analyzed successfully with proposed procedure.